2020
DOI: 10.3389/fpsyg.2020.01333
|View full text |Cite
|
Sign up to set email alerts
|

Biased Affective Forecasting: A Potential Mechanism That Enhances Resilience and Well-Being

Abstract: According to a growing body of studies, people's ability to forecast future emotional experiences is generally biased. Nonetheless, the existing literature has mainly explored affective forecasting in relation to specific events, whereas little is still known about the ability to make general estimations of future emotional states. Based on existing evidence suggesting future-oriented disposition as a key factor for mental health, the aims of the current study were (1) to investigate the relationship between n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 79 publications
1
31
0
Order By: Relevance
“…Participants were prompted three times a day for two weeks to complete a brief questionnaire on their smartphone, reaching a total of 42 potential observations for each participant. Consistent with previous studies, this sampling frequency has been shown to be adequate for the assessment of daily emotion regulation patterns [18] and it leads to good compliance levels [16,17]. In the present study, 2726 out of 3570 possible assessments were obtained, thus revealing a mean compliance of 76.34% (SD = 18.12), ranging between 33% and 100%.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Participants were prompted three times a day for two weeks to complete a brief questionnaire on their smartphone, reaching a total of 42 potential observations for each participant. Consistent with previous studies, this sampling frequency has been shown to be adequate for the assessment of daily emotion regulation patterns [18] and it leads to good compliance levels [16,17]. In the present study, 2726 out of 3570 possible assessments were obtained, thus revealing a mean compliance of 76.34% (SD = 18.12), ranging between 33% and 100%.…”
Section: Methodssupporting
confidence: 89%
“…These strategies are implemented not only during the experience of a positive emotional state [ 10 ]. They might also be used before (i.e., while anticipating a positive event) [ 16 ] or after (i.e., while recalling a positive memory) [ 17 ] the emotion-generative process [ 10 , 11 ]. For the purposes of the present study, however, we will mainly focus on the available literature exploring PE regulation in the present.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, our model is the first to test the unique contribution of momentary mood to QoL together with additional potential contributors. It could be that the robust finding regarding the mediating role of momentary mood in our model is due to the absence of daily mood reporting in previous models accounting for QoL to date (48,93). The fact that momentray mood was such a strong predictor of QoL may be accounted for by the high ecological validity of repeated momentary mood assesment, which assesses mood in the current moment and in a real world setting (39,42).…”
Section: Momentary Mood As a Significant Contributor To Qol Predictionmentioning
confidence: 87%
“…In addition, female adolescents show greater variability in EMA of mood compared with male adolescents ( 46 , 47 ). Recent studies have further shown that daily positive affect is associated with higher QoL and lower depressive and anxiety symptoms, through the enhancement of psychological resilience ( 48 , 49 ).…”
Section: Introductionmentioning
confidence: 99%
“…More generally, studies have found that positive illusionssuch as unrealistic optimism-also yield psychological benefits in the face of risky or uncertain situations (Taylor and Brown, 1994;McKay, 2009;Makridakis and Moleskis, 2015), increasing motivation and promoting resilience in response to adversity (Bénabou and Tirole, 2002;Johnson and Fowler, 2011;Kleiman et al, 2017). For example, research has found that individuals who are unrealistically optimistic about how positively they will feel in the future are better able to handle stress (Colombo et al, 2020). Others have shown that college students with more optimistic expectations for their academic performance invest more quality effort into studying and are more satisfied with their decision-making (Lench et al, 2021).…”
Section: Evolution and Unrealistic Optimismmentioning
confidence: 99%